Wildlife-Friendly Landscaping: Connecting Professionals and the Public: AEC789/WC450, 1/2024 - Kalauni, Dharmendra; Warner , Laura A.; Marois, Emily; Diaz, John M.; Dale , Adam; Daniels, Jaret (EDIS, 2024)
<!–StartFragment –>In the United States, the green industry is a billion-dollar sector that generates millions of employment opportunities annually. Green industry professionals, homeowners, and renters all play important roles in deciding how to design and maintain urban and residential landscapes. Decades of research have shown a need to accommodate wildlife and pollinator conservation efforts in urbanized landscape design and maintenance. The studies summarized in this publication were designed to evaluate the perceptions of green industry professionals and consumers regarding wildlife-friendly landscape maintenance practices to develop insights for future landscape conservation efforts that protect wildlife in Florida’s and the US’s rapidly expanding urban areas. This publication is intended for program planners, educators, Extension agents, green industry professionals, policymakers, and researchers working to promote pollinators and biodiversity in urban and residential landscapes. <!–EndFragment –>